Orthostatic Hypotension Is Associated With Cognitive Decline in Parkinson Disease - Longardner, Katherine; Bayram, Ece; Litvan, Irene (Frontiers in Neurology, 2020)
Introduction: Cognitive impairment and orthostatic hypotension (OH) are common, disabling Parkinson disease (PD) symptoms that are strongly correlated. Whether the relationship is causative or associative remains unknown. OH may occur without classic orthostatic symptoms of cerebral hypoperfusion (i.e., lightheadedness or dizziness). Whether longitudinal differences in cognition occur between symptomatic and asymptomatic OH patients has not been explored. Objectives: We characterized the prevalence of OH, orthostatic symptoms, and cognitive impairment among PD patients and compared cognition between patients with and without OH, and between patients with symptomatic and asymptomatic OH. Methods: Our cross-sectional, retrospective, observational study included 226 clinically diagnosed PD patients who underwent repeated standardized evaluations. Among these, 62 had longitudinal follow-up of > 3.5 years. We compared longitudinal Montreal Cognitive Assessment (MoCA) scores between patients remaining OH-free (n=14) and those without baseline OH that developed OH (n=28), matched for age, sex, education, and PD duration. We also compared MoCA scores between groups with asymptomatic OH (n=13) and symptomatic OH (n=13) matched for the same factors. Results: In the cross-sectional analysis, OH patients had worse cognition. In the longitudinal analysis (mean follow-up = 5.3 years), OH patients had worse cognitive decline (p=.027). Cognitive impairment was similar between asymptomatic and symptomatic OH patients in the cross-sectional and longitudinal analyses. Conclusions: OH is associated with cognitive impairment in PD. Further studies are needed in larger cohorts to expand our findings and to determine whether treating OH can prevent or delay cognitive dysfunction.